2009
DOI: 10.1038/ng.501
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies five loci associated with lung function

Abstract: Pulmonary function measures are heritable traits that predict morbidity and mortality and define chronic obstructive pulmonary disease (COPD). We tested genome-wide association with forced expiratory volume in 1 s (FEV1) and the ratio of FEV1 to forced vital capacity (FVC) in the SpiroMeta consortium (n = 20,288 individuals of European ancestry). We conducted a meta-analysis of top signals with data from direct genotyping (n ≤ 32,184 additional individuals) and in silico summary association data from the CHARG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
516
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 523 publications
(552 citation statements)
references
References 39 publications
28
516
3
3
Order By: Relevance
“…Furthermore, NDUFC2 may represent a novel oncogene involved in breast cancer and intestinal adenocarcinoma, predicting poor prognosis 39, 40. Notably, the pathological relevance of NDUFC2/rs11237379 has been also highlighted through genome‐wide association studies in pulmonary disease 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NDUFC2 may represent a novel oncogene involved in breast cancer and intestinal adenocarcinoma, predicting poor prognosis 39, 40. Notably, the pathological relevance of NDUFC2/rs11237379 has been also highlighted through genome‐wide association studies in pulmonary disease 41, 42…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of many small candidate gene studies have been inconsistent (9,10). Genomewide association studies (GWASs) of COPD (11)(12)(13) have, to date, identified three susceptibility loci that have been well replicated (14)(15)(16)(17)(18)(19)(20)(21). We report the results of a follow-up GWAS in four cohorts that identifiy a new COPD susceptibility locus.…”
Section: Introductionmentioning
confidence: 99%
“…Even in normal healthy individuals there is variation in lung function. Meta-analysis of genome-wide studies (16 studies totaling >40,000 individuals) identified loci associated with natural variations in lung function of healthy volunteers (Hancock et al, 2010;Repapi et al, 2010). These loci included HHIP and PTCH1 which are both required for lung development in mice (Chuang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%